Evaluation of dry eye-associated symptoms and signs after microincision cataract surgery - Ozyol, Pelin; Ozyol, Erhan (The European Research Journal, 2016)
Objectives. To evaluate the effects of microincision cataract surgery on dry eye-associated symptoms and signs. Methods. This prospective study included 40 eyes of 32 patients. Microincision cataract surgery was performed to eyes through 2.2 mm superior clear corneal incision. Dry eye-associated symptom scoring, corneal sensitivity test, Schirmer 1 test, tear break-up time (tBUT) were measured at 3 days before and 3 days, 10 days, 1 month, 3 months after surgery. ‘One way ANOVA for repeated measures’, and Pearson correlation tests were used for statistical analysis. Results. The postoperative symptom scores were significantly different from preoperative value at all consecutive examinations (p